ANALISIS PEMASARAN KOMODITI PANILI (Studi kasus di Propinsi Sulawesi Utara) - TJETEP NURASA; ADE SUPRIATNA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
This study was conducted in 2002 dan took place in Province of North SulawesiNorth. Sub-Province of Minahasa as one of the North Sulawesi center of vanilla productionwas chosen for location of study. The objectives of study were: (i)to analyze theprofitability of vanilla farm, ( ii) to identify the channel of vanilla marketing dan, itsmargin in each agent of marketing, dan ( iii) to analyze the role of attribute of productquality to vanilla price. Research used method of survey structure. Primary data werecollected from 60 farmers, 15 merchants, 5 product processing, dan 2 exporters. Whilesecondary data were collected from Central Agency of Statistics, the Office of EstateCrops, reports of Research Institute, dan others relating to this study. Results showed, thatin one cycle of production ( 10 year), vanilla farm required production cost about Rp.86,4million per hectare consisting of labor fee ( 82,7%), input productions ( 11,4%), dan othercosts ( 5,9%). It took a total production of Rp.209,3 million dan a total income ofRp.122,9 million per hectare. Efficiency rate of vanilla farm was enough high. Withinterest rate 24 dan 30 %, vanilla farm reached B/C Ratio of 3,58 dan 2,45, dan reachedNPV of Rp.35,03 million dan Rp.26,07 million, respectively. Value of IRR indicated thatvanilla farm would reach break-even point in interest rate of 74,6 percent. The channel ofvanilla marketing was still modestly, farmer as vanilla producer at most selling to small(collecting) merchant ( 50%), large merchant ( 40%), dan large merchant/exporter ( 10%).A highest marketing margin was obtained by large merchant/exporter (Rp.7.000/kg), largemerchant (Rp.4.495/kg), dan small merchant (Rp.1.885/kg). The price of vanilla wasdetermined by diameter, long, dan color of fruit where long of fruit gave a biggestparameter, namely 0.67. It means that accretion of fruit length equal to 10 percent willimprove the vanilla price equal to 6.7 percent. Some suggestions to increasing productivitydan quality of vanilla product were; ( i) knowledge dan skilled of farmer have to beimproved continuously in line with the increasing of new innovation, ( ii) role of farmergroup have to be improved, dan (iii) private sector as agent of agribusiness like productprocessing dan exporter have to include in assisting farmer. Their participation were veryexpected to assist farmer, especially in maintaining vanilla crops, supplying input ofproduction, dan marketing.